Fact-checking e democracia: a cartada truco nas eleições presidenciais no Brasil (2018) - Cabral, Umberlândia Alves (2019)
We analyzed in this research the project of fact-checking Truco (2014-1018), based by Agência Pública (2011). It is a checking work of public figures declarations and political information. Some of the aspects examined include identifying the profile of the fact-checker, professional responsible for checking information, and verify how he fits in the current journalistic standard; differentiate the fact-checking format from other journalistic practices and evidentiate the relationship between the format and the functions of gatekeeping and gatewatching. We did a reflection about Truco's checks referring to the second round of presidential elections (2018) and we verified that the project checks are conducted by the public interest, central element in the search for democratic participation.